2016
DOI: 10.1038/srep20099
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient allocation strategies of woody plants: an approach from the scaling of nitrogen and phosphorus between twig stems and leaves

Abstract: Allocation of limited nutrients, such as nitrogen (N) and phosphorus (P), among plant organs reflects the influences of evolutionary and ecological processes on functional traits of plants, and thus is related to functional groups and environmental conditions. In this study, we tested this hypothesis by exploring the stoichiometric scaling of N and P concentrations between twig stems and leaves of 335 woody species from 12 forest sites across eastern China. Scaling exponents of twig stem N (or P) to leaf N (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 45 publications
(76 reference statements)
2
46
1
1
Order By: Relevance
“…The three tissues showed consistent relationships under greenhouse conditions, which could be the result of their interdependent nutrient acquisition. However, the values of the scaling exponents found by us are quantitatively distinct from those previously reported (Kerkhoff et al 2006, Yuan et al , Zhao et al ), partly because the needles, stems and roots of spruce seedlings generally exhibit high metabolic activity and require high nutrient investments to meet the demands of important physiological processes in the early juvenile phase of development. For example, the N and P in needles are crucial components in the photosynthetic apparatus, whereas the N and P in stems and roots have important roles in phloem loading and the export of photosynthates (Marschner and Marschner ), internal nutrient recycling (Marschner et al ), and respiration (Reich et al ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The three tissues showed consistent relationships under greenhouse conditions, which could be the result of their interdependent nutrient acquisition. However, the values of the scaling exponents found by us are quantitatively distinct from those previously reported (Kerkhoff et al 2006, Yuan et al , Zhao et al ), partly because the needles, stems and roots of spruce seedlings generally exhibit high metabolic activity and require high nutrient investments to meet the demands of important physiological processes in the early juvenile phase of development. For example, the N and P in needles are crucial components in the photosynthetic apparatus, whereas the N and P in stems and roots have important roles in phloem loading and the export of photosynthates (Marschner and Marschner ), internal nutrient recycling (Marschner et al ), and respiration (Reich et al ).…”
Section: Discussioncontrasting
confidence: 88%
“…It has been found that the scaling exponent ( α ) of N to P is significantly smaller than 1 within organs (an allometric scaling relation) (Niklas et al 2005, Elser et al , Han et al ). The allometric scaling exponent of N and P has also been studied across organs (Yuan et al , Yan et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The strategies of the rate of allocating the limiting elements in different organs are vital for them to respond to the environmental changes. However, most of studies (Garten 1976, Wright et al 2004, Reich et al 2010, Yang et al 2014, Yan et al 2016) have focused on specific organs, especially leaves and roots. There are still big gaps in understanding the strategies employed by the whole plants to allocate these limiting elements.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors are likely involved. For example, the length of the growing season, and thus leaf longevity tend to decrease from the tropics to boreal regions, resulting in higher leaf growth rates and higher P demands, particularly in the growing season, with increasing latitude [41,46]. Furthermore, soil P availability relative to N availability tends to increase with increasing latitude or from the humid to arid regions, resulting in decreasing leaf N:P ratios [10,31,32,47].…”
Section: Possible Mechanisms Of the Different N-p Scaling Exponentsmentioning
confidence: 99%